Ependymoma with Intraorbital Extracerebral Recurrence: Case Report - Macêdo, Lívio Pereira de; Vale, Benjamim Pessoa; Araújo, Marx Lima de Barros; Vale, João Cícero Lima; Ferreira, Yally Dayanne Oliveira; Araújo, Suelen Maria Silva de (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Ependymomas are rare neuroepithelial tumors that originate from a type of glial cell called ependymal cell. In general, they correspond to ∼ 1.2 to 7.8% of all intracranial neoplasms, and to ∼ 2 to 6% of all gliomas. Although it corresponds only to ∼2 to 3% of all primary brain tumors, ependymoma is the fourth most common cerebral neoplasm in children, especially in children younger than 3 years of age.12 In patients younger than 20 years of age, the majority (90%) of ependymomas are infratentorial, more precisely from the IV ventricle. In spite of this, in adults, medullary ependymomas are more frequent (60%). In this context, supratentorial and extraventricular ependymomas, as in the case reported in the present article, are infrequent in both adults and children.12 Both sexes are equally affected.3 Recurrence of intracranial ependymomas occurs in almost 50% of the cases, and the follow-up outcome is not favorable.4 In another perspective, the recurrence of extracerebral ependymomas is extremely rare, and even more unusual in the intraorbital site, as it occurred in the case in question.
Keywords: ependymoma; ependymal cell; anaplastic ependymoma; supratentorial glioma